2018
DOI: 10.1093/jjco/hyy081
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characteristics of defective mismatch repair epithelial ovarian cancer in a Japanese hospital-based population

Abstract: The prevalence of defective mismatch repair epithelial ovarian cancer in the Japanese hospital-based population was extremely low. Molecular mechanism involved in such defective mismatch repair ovarian cancers seems to be epigenetic events through MLH1 promotor hypermethylation or somatically mutated mismatch repair genes without germline mismatch repair mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 40 publications
0
31
0
1
Order By: Relevance
“…Of these 9 (4%) were reported as isolated MLH1, 82 (38%) had MLH1/PMS2 loss, 2 (1%) had isolated MSH2, 54 (25%) had isolated MSH6 loss and 68 (32%) had MSH2/MSH6 loss. Reflex MLH1 promotor hypermethylation data was reported in nine studies 23‐26,32,33,71,75,76 . Of the 53 OCs with MLH1 or MLH1/PMS2 loss 40 (75%) were found to be hypermethylated.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Of these 9 (4%) were reported as isolated MLH1, 82 (38%) had MLH1/PMS2 loss, 2 (1%) had isolated MSH2, 54 (25%) had isolated MSH6 loss and 68 (32%) had MSH2/MSH6 loss. Reflex MLH1 promotor hypermethylation data was reported in nine studies 23‐26,32,33,71,75,76 . Of the 53 OCs with MLH1 or MLH1/PMS2 loss 40 (75%) were found to be hypermethylated.…”
Section: Resultsmentioning
confidence: 95%
“…Of the 53 OCs with MLH1 or MLH1/PMS2 loss 40 (75%) were found to be hypermethylated. Eighteen studies provided information on the FIGO stage in their MMRd IHC cohort 23,24,31‐34,36,37,39,45,47,49,53,55,60,61,71,76 . In total, 71 (38%) were stage I‐II and 118 (62%) were stage III‐IV.…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that methylation is the cause of loss of MLH1 expression, which is observed in colorectal and uterine cancers, whereas loss of MSH2 expression may be due to somatic mutations in both alleles in addition to methylation. Tajima et al ( 44 ) reported that somatic mutations were also detected in both of these alleles in uterine carcinoma. In the present study, the five patients with loss of MMR protein expression did not survive and it was therefore impossible to perform an additional detailed genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively new and with the understanding of its pathogenesis still evolving, the term LLS in association with CRC was first coined in 2013 [29] and, where it has not been described in patients with SBC, the term has come to be used for patients with LS-associated tumors such as CRC [14], epithelial ovarian cancer [30], sebaceous tumors [31], and upper urothelial cancer [32]. LLS may account for as many as 70% of all cases with suspected LS [29].…”
Section: Discussionmentioning
confidence: 99%